Hubungan Perencanaan Karier dan Efikasi Diri dengan Kesipan Kerja Mahasiswa - Latif, Abdul; Yusuf, A Muri; Efendi, Z Mawardi (Universitas Negeri Padang, 2017)
This research was conducted by a high amount of unemployment from graduate students of university. The high amount of unemployment from graduate students of university indicated that undergraduate students had low work readiness. Career planning and self-efficacy were the factors assumed that influenced work readiness. This research was intended to describe: (1) career planning, self-efficacy, and work readiness of undergraduate students, (2) the correlation of career planning with work readiness, (3) the correlation carrier planning and self-efficacy with work readiness. This research applied correlational descriptive research with quantitative method. The population of this research was the seventh and ninth undergraduate students semester of Guidance and Counseling of UIN Suska Riau consisting of 139 undergraduate students, the sample consisted of 103 undergraduate students chosen by using proportional stratified random sampling technique. The instrument used was likert scale model. The data were analysed byÂ using descriptive statistic, simple regression and multiple regression. The research findings indicated that: (1) career planning of undergraduate students was averagely included into good category, self-efficacy of undergraduate students was averagely included into high category, work readiness of undergraduate students was averagely included into high category, (2) there was a significant correlation between career planning with work readiness about 28,7% (R = 0,536, significance 0.000), (3) there was a significant correlation between self-efficacy with work readiness about 16.4% (R = 0.405, significance 0.000), (4) there was a significant correlation between carrier planning and self-efficacy with work readiness about 33.2% (R = 0.576, significance 0.000)Â